2010
DOI: 10.1002/ejlt.200900191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of cast resin based on different saturation epoxidized soybean oil

Abstract: Acrylated epoxidized soybean oils (AESOs) with different level of saturation were obtained by the ring opening of different saturation epoxidized soybean oils using acrylic acid as the ring opener. AESO-based thermosets have been synthesized by free radical polymerization of these AESOs and methyl methacrylate. The thermal properties of these resins were studied by differential scanning calorimetry and thermo-gravimetric analysis. The results indicated that the thermal stability of these resins depends upon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Countless functionalizations of oleochemicals have already been implemented [5]. The carbon-carbon double bonds of fatty acids, fatty esters, and triglycerides have especially been converted into epoxy [6][7][8][9][10][11][12][13], hydroxyl [14][15][16][17][18][19][20][21], formyl [22][23][24][25][26][27], acrylate [28][29][30], or crossmetathesis derivatives [31][32][33], to name only a few. The functionalization of the carbon-carbon double bonds by amino groups is also of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Countless functionalizations of oleochemicals have already been implemented [5]. The carbon-carbon double bonds of fatty acids, fatty esters, and triglycerides have especially been converted into epoxy [6][7][8][9][10][11][12][13], hydroxyl [14][15][16][17][18][19][20][21], formyl [22][23][24][25][26][27], acrylate [28][29][30], or crossmetathesis derivatives [31][32][33], to name only a few. The functionalization of the carbon-carbon double bonds by amino groups is also of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Amino vegetable oils are mainly being synthesized through epoxy ring‐opening of epoxidized oils . However, as the ring‐opening reaction does not proceed readily with internal epoxide, high reaction temperatures, and catalysts are often required . Another approach to obtain amino vegetable oils consists in a four‐steps procedure where the CC double bonds are first converted into polyhydroxy oils which then undergo oxidization to yield polyketones.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recent shift on green or ecological issues that have taken place in society in general, research on naturally-based, thermoset polymers is taking on an ever increasing importance as these materials can be used to substitute the traditional thermo-stable petrochemical polymers, which are difficult to recycle. For this reason, there is a great deal of current research work on epoxidized vegetable oils, such as linseed oil, soybean oil, rape seed oil, castor oil and sunflower oil as a base for ecological, thermoset polymers [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylation of epoxidized vegetable oils is one of the interesting techniques for preparing the vegetable oil-based polymers. The mechanical and thermal properties of acrylated epoxidized soybean oil (AESO) have been reported [3,5,8,20,23,38,39]. It has been established that AESO shows higher mechanical properties than ESO [22,39].…”
mentioning
confidence: 99%
“…It has been established that AESO shows higher mechanical properties than ESO [22,39]. AESO has been used for copolymerization with other materials such as a vinyl ester resin containing styrene [8][9][10] and with poly(methyl methacrylate) [38][39][40]. It was found that the mechanical properties of an AESO-co-PMMA copolymer were higher than those of AESO.…”
mentioning
confidence: 99%